2017
DOI: 10.1038/srep42874
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor is subjected to glucose modification and oxidation in Alzheimer’s Disease

Abstract: Glucose and glucose metabolites are able to adversely modify proteins through a non-enzymatic reaction called glycation, which is associated with the pathology of Alzheimer’s Disease (AD) and is a characteristic of the hyperglycaemia induced by diabetes. However, the precise protein glycation profile that characterises AD is poorly defined and the molecular link between hyperglycaemia and AD is unknown. In this study, we define an early glycation profile of human brain using fluorescent phenylboronate gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…Along this line of research using an early glycation profile of human brain by fluorescent phenylboronate gel electrophoresis Kassaar et al identified early glycation and oxidation of MIF in the AD brain [67]. This modification inhibits MIF enzyme activity and ability to stimulate glial cells.…”
Section: Dysregulayed Balance Of Oxidized and Reduced Isoforms Of Mifmentioning
confidence: 99%
See 1 more Smart Citation
“…Along this line of research using an early glycation profile of human brain by fluorescent phenylboronate gel electrophoresis Kassaar et al identified early glycation and oxidation of MIF in the AD brain [67]. This modification inhibits MIF enzyme activity and ability to stimulate glial cells.…”
Section: Dysregulayed Balance Of Oxidized and Reduced Isoforms Of Mifmentioning
confidence: 99%
“…The authors propose that the demonstrated inability of glycated and oxidized MIF in stimulating glial cells in vitro may represent an important primum movens in defective clearance of plaques from CNS phagocytes during the development of AD. Inferring from this, the augmented CSF and peripheral levels may be part of a homeostatic attempt that, in an unsuccessful way, ultimately aims at counteracting the endogenous functional deficiency of cerebral glycated and oxidized MIF [67]. MIF deficiency attenuates tau hyperphosphorylation in astrocytes from APP/PS1 transgenic mice [58] MIF overexpression prevents Aβ toxicity in SH-SY5Y cells [68] APP23/MIF +/− mice show significant memory impairment [68] Lending support to the concept that MIF may be protective in AD, a recent study has found that MIF expression was upregulated in the brain of AD patients and animal models [68].…”
Section: Dysregulayed Balance Of Oxidized and Reduced Isoforms Of Mifmentioning
confidence: 99%
“…MIF's role in AD pathology has been investigated in many aspects, including immune response, insulin regulation and oxidative stress (Bacher et al 2010;Kassaar et al 2017). In AD pathology, MIF mainly binds the CD74/ CD44 receptor complex followed by multiple intracellular signaling pathways, such as the activation of the extracellular signal regulated kinase (ERK) 1 and 2, the Phosphoinositid-3-Kinase (PI3K)-Akt signal transduction cascade, Nuclear factor 'kappa-light-chain-enhancer' of activated B-cells (NFκB), and the Adenosinmonophosphat (AMP)-activated protein kinase (AMPK) pathway (Su et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite hyperglycaemia per se not being determined as an essential pathogenic prerequisite for ‘type 3’ diabetes, a recent report from the University of Bath along with colleagues at King's College, London, has indicated that a high dietary consumption of sugar in people, not necessarily with diagnosed diabetes, significantly increases the risk of developing Alzheimer's disease. It is suggested that an excess of glucose intake can lead to glycation and oxidation of an enzyme called macrophage migration inhibitory factor (MIF), an immune regulator, damage to which by these processes may be linked to Alzheimer's disease.…”
Section: Dietary Sugar and Dementia Riskmentioning
confidence: 99%